Paired Box 5 (PAX5) Expression in Poorly Differentiated Neuroendocrine Carcinoma of the Gastrointestinal and Pancreatobiliary Tract: Diagnostic and Potentially Therapeutic Implications. Issue 8 (September 2018) - Ainechi, Sanaz; Mann, Steven A.; Lin, Jingmei; Patil, Deepa; Sheehan, Christine E.; Yang, Zhaohai; Zuo, Chunlai; Lee, Hwajeong
Abstract : Paired Box 5 (PAX5), a well-established B-cell marker, is preferentially expressed in small cell lung carcinoma and regulates the transcription of c-Met, offering a potential for therapeutic target. Its expression in poorly differentiated neuroendocrine carcinoma (PDNEC) of the digestive system has not been systemically evaluated. Archived pathology materials from 38 PDNEC in the gastrointestinal (GI) and pancreatobiliary (PB) tract were reviewed. Representative tumor sections were subject to immunohistochemical stain for PAX5, c-Met, and CD20. The extent of the staining [focal (<10%), patchy (10% to 50%), and diffuse (>50%)] and intensity (1+ to 3+) was evaluated. In total, 38 cases of well-differentiated neuroendocrine tumors from GI/PB tract served as controls. Nuclear PAX5 staining was observed in 16 (42%) cases in total, in 46% (11/24) of large cell neuroendocrine carcinoma, 67% (4/6) of small cell neuroendocrine carcinoma, and 13% (1/8) of mixed adenoneuroendocrine carcinoma, with diffuse (8), patchy (4), or focal (4) staining. The intensity was 3+ (2), 2+ (6), and 1+ (8). PAX5 expression was common in ampullary (4/5) and gastroesophageal junctional/esophageal (5/9) PDNEC. Two (5%) of 38 well-differentiated neuroendocrine tumors were positive for PAX5. Three PAX5 positive PDNEC showed weak cytoplasmic c-Met immunolabeling. CD20 was negative in all tumors. Our data show that PAX5 is commonly expressed in PDNEC of the GI/PB tract including small cell neuroendocrine carcinoma. This observation warrants a cautious approach when interpreting small biopsy of poorly differentiated neoplasms, especially when lymphoma is considered in the differentials. Further study of PAX5/c-Met signaling pathway and its potential therapeutic value in GI/PB PDNEC is warranted.